Do coro à orquestra, da orquestra para o coro : A gestualidade dramático-musical segundo Richard Wagner - Mota, Marcus (Synthesis.)
Composer and playwright Richard Wagner (1813-1883) undertook a gigantic project to receive the dramaturgy of ancient Greek theater. Taking as a basis the stage space in which the plays of Aeschylus, Sophocles and Euripides presented their texts, Wagner proposed transferring the functions of the chorus in the orchestra to the orchestra as a chorus. In his description of this transfer in Opera and Drama (1851), Wagner describes the orchestra of musicians as a body articulated with speech and gestures.This article will present and analyze Wagner's proposal, for which the concept of orchestra-chorus-gesture can clarify procedures for the reception of ancient Athenian drama. As we are dealing with a discontinuous, fragmentary tradition, creative solutions in reception are not limited to their immediate staging context. In Wagner's case, this is even more evident: the German musical playwright produced intense essays and reflections, especially around the Ring of the Nibelung project. In this way, Wagner's creative decisions dialog with a historical mediation that both addresses the partial data of tradition and redefines them in a new staging approach.